The acute effects of pre- and mid-exercise carbohydrate ingestion on the immunoregulatory stress hormone release in experienced endurance athletes—a systematic review - Christ, T.; Ringleb, M.; Haunhorst, S.; Fennen, L.; Jordan, P. M.; Wagner, H.; Puta, C. (Frontiers in Sports and Active Living, 2024)
Background: In times of physical stress, the body orchestrates a multisystemic regulatory response. The hormones epinephrine and norepinephrine play a role in the immediate regulation chain, while cortisol is involved in delayed regulation. The release of those stress hormones in response to exercise has previously been reported to elicit diverse immune reactions.